Recurrent spreading depolarizations after subarachnoid hemorrhage decreases oxygen availability in human cerebral cortex - Bosche, Bert (Wiley Subscription Services, Inc., A Wiley Company, 2010)
OBJECTIVE: Delayed ischemic neurological deficit (DIND) contributes to poor outcome in subarachnoid hemorrhage (SAH) patients. Because there is continuing uncertainty as to whether proximal cerebral artery vasospasm is the only cause of DIND, other processes should be considered. A potential candidate is cortical spreading depolarization (CSD)-induced hypoxia. We hypothesized that recurrent CSDs influence cortical oxygen availability. METHODS: Centers in the Cooperative Study of Brain Injury Depolarizations (COSBID) recruited 9 patients with severe SAH, who underwent open neurosurgery. We used simultaneous, colocalized recordings of electrocorticography and tissue oxygen pressure (p(ti)O(2)) in human cerebral cortex. We screened for delayed cortical infarcts by using sequential brain imaging and investigated cerebral vasospasm by angiography or time-of-flight magnetic resonance imaging. RESULTS: In a total recording time of 850 hours, 120 CSDs were found in 8 of 9 patients. Fifty-five CSDs (∼46%) were found in only 2 of 9 patients, who later developed DIND. Eighty-nine (∼75%) of all CSDs occurred between the 5th and 7th day after SAH, and 96 (80%) arose within temporal clusters of recurrent CSD. Clusters of CSD occurred simultaneously, with mainly biphasic CSD-associated p(ti)O(2) responses comprising a primary hypoxic and a secondary hyperoxic phase. The frequency of CSD correlated positively with the duration of the hypoxic phase and negatively with that of the hyperoxic phase. Hypoxic phases significantly increased stepwise within CSD clusters; particularly in DIND patients, biphasic p(ti)O(2) responses changed to monophasic p(ti)O(2) decreases within these clusters. Monophasic hypoxic p(ti)O(2) responses to CSD were found predominantly in DIND patients. INTERPRETATION: We attribute these clinical p(ti)O(2) findings mainly to changes in local blood flow in the cortical microcirculation but also to augmented metabolism. Besides classical contributors like proximal cerebral vasospasm, CSD clusters may reduce O(2) supply and increase O(2) consumption, and thereby promote DIND. ANN NEUROL 2010;67:607–617